Catalytic steam reforming of real tar under high-efficiency Ni/USY catalyst for H2 production. (15th December 2021) - Gao, Ningbo; Chen, Kailun; Lai, Xiaoyong; Quan, Cui
Highlights: Ni/Y catalyst with high efficiency was prepared by incipient wetness impregnation. High porosity, good dispersion and considerable surface Ni 0 were identified. Excellent activity in terms of tar conversion (81.3%) and H2 yield (87.2 mmol/g) was obtained. Lower apparent activation energy (57.6 kJ/mol) were gained. Reaction mechanism of tar reforming under Ni/Y catalyst was proposed. Abstract: A series of Ni/USY catalysts were developed by incipient wetness impregnation and applied for catalytic steam reforming of coal tar in a two-stage reactor. The reforming conditions, including Ni loading amount (5–20 wt%) and reaction temperature (600–900 °C), were studied. It was found that Ni/USY catalyst showed a superior catalytic activity in terms of tar conversion (81.3%) and H2 yield (87.2 mmol/g) when the Ni loading amount was 15 wt% (i.e. 15NiY) and reaction temperature was 800 °C. The performance of 15NiY in terms of tar conversion decreased slightly after 180 min of reaction and could be recovered easily. According to N2 adsorption-desorption analysis, as-prepared catalysts exhibited excellent porosity and the special surface area was higher than 450 m 2 /g. Ascribed to the high porosity and special structure of Ni/USY, Ni nanoparticles with a size of 10–50 nm were well dispersed, which was observed by XRD and FE-SEM/EDS. H2 -TPR demonstrated the strong metal-support interation of Ni/USY catalysts. The XPS spectra demonstrated that the surface of Ni/USY catalysts were enriched with surface adsorbed oxygen species and the value of Ni 0 /Ni 2+ reached the highest for 15NiY, which facilitated the extent of reaction. In addition, a kinetic model was applied for calculation of apparent activation energy and pre-exponential factor, which were 57.6 kJ/mol and 8.76 × 10 3 m 3 kg −1 catalyst h −1, respectively, indicating the effectiveness of Ni/USY catalyst.